2018
DOI: 10.1002/ijc.31410
|View full text |Cite
|
Sign up to set email alerts
|

PLOD2 as a potential regulator of peritoneal dissemination in gastric cancer

Abstract: Peritoneal dissemination is the most common metastatic pattern in advanced gastric cancer (GC) and has a very poor prognosis. However, its molecular mechanism has not been elucidated. Our study investigated genes associated with peritoneal dissemination of GC. We performed combined expression analysis of metastatic GC cell lines and identified Procollagen-lysine, 2-oxoglutarate 5-dioxygenase2 (PLOD2) as a potential regulator of peritoneal dissemination. PLOD2 is regulated by hypoxia-inducible factor-1 (HIF-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Several studies have suggested that PLOD2 is correlated with poor prognosis of multiple cancers, including sarcoma, lung cancer, renal cell carcinoma, breast cancer, cervical cancer and bladder cancer [19,[27][28][29][30][31]. PLOD2 reinforces the migration capacity of cancer cells, and also promotes cancer cells migration along the "highway" linear collagen [19,28,32]. Previous studies showed silencing of PLOD2 led to the inhibition of migration and invasiveness of multiple cancer cells themselves, which might mediate by abrogating the epithelialmesenchymal transition (EMT) of those cancer cells [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that PLOD2 is correlated with poor prognosis of multiple cancers, including sarcoma, lung cancer, renal cell carcinoma, breast cancer, cervical cancer and bladder cancer [19,[27][28][29][30][31]. PLOD2 reinforces the migration capacity of cancer cells, and also promotes cancer cells migration along the "highway" linear collagen [19,28,32]. Previous studies showed silencing of PLOD2 led to the inhibition of migration and invasiveness of multiple cancer cells themselves, which might mediate by abrogating the epithelialmesenchymal transition (EMT) of those cancer cells [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…4). Mechanistic studies have revealed that PLOD2 can be regulated by numerous factors, including HIF-1α, TGF-ÎČ, EGF, miR 26a/b, IL-6 and leptin [9,19,27,28,32] . The paracrine signals derived from adipocytes or CAFs were reported to regulate PLOD2 expression in multiple cancers, suggesting the signals in microenvironment might involve in regulating PLOD2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Data have shown that TAFs play significant roles in the therapeutic sensitivity of tumors and that therapeutic targeting of TAFs results in increased chemotherapeutic sensitivity in colorectal cancer [29]. PLOD2 is overexpressed in multiple cancers, including GC [17]. However, no study has shown its role in GC chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Among the GC patients, the PLOD2 high group had large amounts of collagen in their cancer tissues. PLOD2 knockdown through siRNA in several GC cell lines suppresses invasion and migration in vitro [17].…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation